Plant Petiole Sap-Testing for Vegetable Crops - George Hochmuth; Robert Hochmuth (EDIS)
Various nitrate and potassium "quick-test" kits for vegetable plant sap-testing have been calibrated for use on Florida vegetables. The objective has been to find a system that growers can use in the field to help manage nitrogen (N) and potassium (K) fertilizer—especially for drip-irrigated vegetables. The following guidelines should help individuals who are currently using—or are interested in using—sap-testing. Revision by George and Robert Hochmuth published by the UF/IFAS Horticultural Sciences Department; 6 pages. https://edis.ifas.ufl.edu/cv004